Urinary NGAL and KIM-1 in Canine Monocytic Ehrlichiosis - Mariana Elisa Pereira; Darlan Henrique Canei; Yolanda Paim Arruda Trevisan; Fernanda Harumi Maruyama; Nathália de Assis Pereira; Eduarda Pavan; Carolina Zorzo; Adriane Jorge Mendonça; Luciano Nakazato; Domingos Tabajara de Oliveira Martins; Juliano Bortolini; Daniel Moura de Aguiar; et al. (Veterinary Sciences)
Glomerulonephritis, caused by the deposition of immune complexes, can lead to kidney damage in dogs with canine monocytic ehrlichiosis (CME). The early diagnosis of renal insult is important to prevent severe kidney disease in infected dogs by Ehrlichia canis. This study aimed to investigate urinary biomarkers of renal function, neutrophil gelatinase (uNGAL), and kidney injury molecule-1 (uKIM-1) using the Luminex® xMAP® platform, and the proportion of mixed or high molecular weight proteinuria in dogs with CME. This study included blood samples of thirty dogs with clinical signs of CME and amplified DNA for E. canis (CME group) and six dogs of different breeds and both sexes, aged 3 to 7 years, that showed no clinical-laboratory alterations or tick parasitism and were tested negative for E. canis via PCR (control group). The total calcium, phosphorus (p < 0.05), urea (p < 0.001), creatinine (p < 0.05), urinary density (p < 0.05), urinary protein creatinine ratio (p < 0.001), uNGAL (p < 0.05), and uKIM-1 (p > 0.05), as well as the proportion of high molecular weight proteinuria and mixed proteinuria (p < 0.01), were measured. Elevated serum concentrations of creatinine, urea, and phosphorus combined with reduced urinary density, increased urinary creatinine–protein ratio, urinary NGAL, and mixed proteinuria detected renal damage in dogs with CME, while KIM -1 remained unchanged. uNGAL can detect early renal lesions, reflecting renal damage before a significant increase in serum creatinine occurs, and appears to be an early diagnostic biomarker in renal disease in dogs with CME.